Does Industry 4.0 improve productivity? Evidence from the Italian automotive supply chain. (2nd November 2022) - Calabrese, Giuseppe Giulio; Falavigna, Greta
This paper aims at investigating the diffusion, application, constraints and performance of the implementation of Industry 4.0 technologies in the Italian automotive supply chain. The worldwide positioning of Stellantis is likely to move the Italian automotive industry from a core automotive country like the USA, Germany, or Japan to a semi-peripheral automotive country like the UK, Canada or Sweden focused mainly on the supply chain. The Italian automotive supply chain is one of the most relevant in Europe with more than 2, 000 firms and covers all product specialisation. In the digitalisation transition era, Industry 4.0 holds potential to reshape and reinforce existing regional supply chains. Literature suggests better performance for whom invested in Industry 4.0; however our findings did not match expectations although some interesting exceptions emerge.